Commensal Rat Pests And Their Control Using Anticoagulant Rodenticides In Urban Areas In Penang Island - Sukri, Wan Nur Amni Wan Ahmad (2018)
The abundance and composition of commensal rats in Penang Island were evaluated using direct method of live-trap sampling method. Bait preferences of rat were also analyzed with the highest number of trap success (35.56%) recorded when live-traps were baited with fried chicken leftover compared with other type of baits as determined by one-way ANOVA (p<0.05). In this study, there were five different species of commensal rats caught throughout of the study. The dominant species in commercial areas was Rattus norvegicus and in residential areas was Bandicota bengalensis. The laboratory efficacy, palatability and bait acceptance of selected anticoagulant rodenticides, bromadiolone and chlorophacinone were evaluated using wild R. norvegicus as samples. Bromadiolone and chlorophacinone bait recorded 100% of mortality in no-choice feeding experiment. For choice-feeding test, 77% mortality rate was recorded for rats treated with bromadiolone bait meanwhile 33% of mortality was recorded on chloropacinone bait treatment. The results indicate high efficacy of both rodenticides against Norway rats. Bromadiolone bait recorded 24.12% bait acceptance while chlorophacinone recorded 12.97%. The palatability ratio of bait against normal diet showed bromadiolone at (1:3) while chlorophacinone at (1:7). The results of bait acceptance and palatability ratio indicated bait formulation of bromadiolone was highly attractive to rats as compared to chlorophacinone bait formulation. Next, the field efficacies of both rodenticides were evaluated for 60 days. The bait acceptance impact of the treatments on rat population and reduction of rat activity at the treatment sites were assessed throughout of the study. The bait acceptance for bromadiolone treatment was 26% from the total bait offered during seven days of baiting period. Whereas for chlorophacinone, only 4% from the total of bait offered was consumed during 7 days of baiting period. The number of carcasses found at bromadiolone treatment site was 15 meanwhile at chlorophacinone treatment site, only one carcass was found. The reduction of population was 83.57% at 60 days after treatment in bromadiolone treatment site whereas 55.94% in chlorophacinone treatment site. This indicates that bromadiolone was more effective compared to chlorophacinone against commensal rats. Furthermore, HPLC analysis showed the detection of residue in liver of rat samples can be used to indicate exposure of rats to both compounds. The amount of residue detected in liver of rat samples for bromadiolone was 0.00309±0.0010mg/ml or equivalent to 12.88% from the total compound consumed for 6 days in no-choice feeding tests. Meanwhile, residue retained in the liver of rat samples for chlorophacinone was 0.001±0.00004mg/ml or equivalent to 5.56% the total of compound consumed for 6 days in no-choice feeding. This suggests that the amount of bromadiolone compound retained in the liver of the rat was higher than chlorophacinone.